THE INFLUENCE OF INVENTORY AND DISTRIBUTION TOWARD LPG SALES VOLUME IN PT OPTIMA SINERGI COMVESTAMA SEMARANG - Danny Christian De Rosal; Achmad - Zaenuddin; Agus - Suratno (Politeknik Negeri Semarang, 2019)
The purposes of this study were to analyze the influence of Inventory (X1) and Distribution (X2) as independent variables on LPG Sales Volume (Y) as dependent variable individually and to find out how many contributions of all independent variables to dependent variable. Multiple Linear Regression Analysis method by IBM SPSS 23 was used in this study equipped with the Classic Assumption Test and Coefficient of Determination. Data used in this study were secondary data collected from PT. Optima Sinergi Comvestama from January 2016 to December 2018. The result of F-test in this study showed that simultaneously and significantly, all of independent variables influenced dependent variable even though T-test result showed that partially, Inventory and Distribution have a positive significant influence on LPG Sales Volume. However, based on the coefficient of determination test, it was found that Inventory and Distribution have a high contribution in explaining LPG Sales Volume that is 93,2%. In addition, the multiple linear regression analysis result with the model Y= -6793558,110 + 1,004 + 1,015 showed that if there were an increase in Inventory and Distribution then LPG Sales Volume would also increase